Profil Fitokimia dan Aktivitas Antibakteri Bunga Kekara Laut (Canavalia rosea) Menggunakan Metode Difusi Cakram - Idrus, Irman; Nasrun, Efa Kelya; Ramandha, Muhammad Eka Putra (Department of Pharmacy, Bumigora University, 2024)
Bacterial infection is one of the leading causes of chronic diseases and ongoing risks of mortality that continuously threaten public health globally. Improper use of antibiotics can lead to pathogenic bacteria developing resistance to antibiotics and cause dangerous side effects. Therefore, searching for alternative antibiotic sources derived from natural materials is essential. One type of plant that has the potential as an antibacterial agent is Canavalia rosea. This research aims to qualitatively assess the phytochemical content using tube methods and evaluate the antibacterial activity of the ethyl acetate fraction of Canavalia rosea extract using the disc diffusion method. Canavalia rosea leaves were extracted using a maceration method using 96% ethanol, and fractionation was done using ethyl acetate. Phytochemical analysis showed alkaloid, saponin, flavonoid, polyphenol, and tannin compounds in the Canavalia rosea flower extract. The antibacterial activity of the ethyl acetate fraction of the extract showed a significant inhibition zone against the growth of Staphylococcus aureus bacteria. At a concentration of 9 mg/mL, the inhibition zone reached 20.31 ± 0.27 mm, falling into the moderate to strong category. While at a concentration of 1.5 mg/mL, the inhibition zone reached 5.13 ± 0.32 mm, indicating lower inhibitory effects. Statistical analysis showed that the ethyl acetate fraction of Canavalia rosea extract has significant antibacterial activity, with each concentration having different effects in inhibiting the growth of S. aureus.